Linking GIS and Remote Sensing Data to Study Vegetation Patterns - Polina Lemenkova (O. Yu. Gerasimova, E. L. Gunicheva, G. S Mullagayanova, 2015)
В статье рассматривается использование геоинформационных технологий (ГИС) для обработки спутниковых снимков для мониторинга изменения ландшафтов в течение двух десятилетий. Методология работы направлена на техническое применение инструментов дистанционного зондирования и ГИС для изучения растительного покрова в тундре экосистем методом классификации снимков. Схема обработки снимков включает составление цветных композитов, георефенцирование, управляемая классификация по эталонным пикселям. Данные включают в себя сцены Ландсат (Landsat TM). The paper studies changes in land cover types in tundra landscapes during the past two decades. The study area is located in the Yamal Peninsula, north-central Russia. The main objective of this research is to analyse changes in vegetation distribution and land cover types over the area of Yamal Peninsula. Methodology of the work aims at technical application of the remote sensing and GIS tools for studies and includes georeferencing, creation of colour composites, supervised classification. The research data includes Landsat scenes.